Model-informed drug development approach supporting approval of the 4-week (Q4W) dosing schedule for nivolumab (Opdivo) across multiple indications: a regulatory perspective. (2nd February 2019) - Bi, Y; Liu, J; Furmanski, B; Zhao, H; Yu, J; Osgood, C; Ward, A; Keegan, P; Booth, B P; Rahman, A; Wang, Y
Abstract: Background: A nivolumab dosage regimen of 480 mg intravenously (i.v.) every 4 weeks (Q4W) was approved by FDA for the majority of the approved indications for nivolumab. Methods: The proposed new dosage regimen was supported by pharmacokinetic modeling and simulation, dose/exposure–response relationships for efficacy and safety in the indicated patient populations, and the clinical safety data with the 480 mg Q4W dosage regimen. Pharmacokinetic exposures achieved with 480 mg Q4W were predicted for 4166 patients in 21 clinical studies with various types of solid and hematological tumors. Exposure–response analyses were conducted to predict 480 mg Q4W safety and efficacy across all FDA-approved indications for nivolumab. Results: For the overall population, the geometric mean exposure achieved with 480 mg i.v. Q4W was 5.2% higher for steady state C avg and 15.6% lower for C trough than those with 3 mg/kg i.v. Q2W, the approved dosage regimen. The simulated concentration–time course achieved with 480 mg Q4W regimen was below the median concentration achieved with 10 mg/kg i.v. Q2W that was also studied in clinical trials. The predicted probability of adverse events was similar between 480 mg Q4W and that observed with the 3 mg/kg Q2W regimen. Efficacy results were found to be similar between Q2W and Q3W dosage regimens in patients with renal cell carcinoma. The predicted efficacy for each indication suggested that the efficacy with 480 mg Q4W is unlikely to be compromised compared with that observed with 3 mg/kg Q2W. Conclusions: The model-informed analyses of predicted exposure, efficacy and safety based on data from extensive clinical experience with nivolumab suggest that the benefit–risk profile of 480 mg Q4W regimen is comparable to the approved 3 mg/kg Q2W regimen, thus providing the regulatory basis for the approval of 480 mg Q4W regimen in the absence of clinical efficacy data with this new dosage regimen.